Analisis Sistem Berpikir Fenomenologis dalam Pemikiran M.A.W. Brouwer: Studi Islam terhadap Buku Psikologi Fenomenologis - Syafii, Fadhil Ridwan; Sukiman, Sukiman; Faza, Abrar M. Dawud (TSAQOFAH, 2024)
The book entitled "Psychological Phenomenology" contains many things related to the discussion of phenomenology which are packaged in more depth. In this research, the researcher wants to explore the scope of what is included in the study of phenomenology and study leading phenomenological figures and their theories that influence the phenomenological thinking of M.A.W. Brouwer. The aim of this research is to provide more in-depth knowledge regarding the thoughts of a M.A.W. Brouwer and his substance regarding phenomenological studies from his point of view. In this research, researchers used a type of library research (Library Research). The object of this research is a book by M.A.W. Brouwer entitled Phenomenological Psychology and several supporting literature to strengthen the reference material for this research. This research activity consists of reading book texts, reading several other reading materials regarding the main characters of the research and identifying the ideas of the characters' thoughts so that it becomes a research unit that is informative but also philosophical. The results of this research explain that although M.A.W. Brouwer never considered himself a phenomenologist and had a theory regarding phenomenology, but much of the substance of his thinking tended to analyze many figures to become a source of knowledge for him.